MODEL DUKUNGAN SOSIAL UNTUK MENURUNKAN KECEMASAN PEREMPUAN MENOPAUSE DI KECAMATAN DIWEK KABUPATEN JOMBANG - Khotijah, Siti (WELL BEING, 2018)
Menopause is a developmental phase or natural change of women’s lives when menstrual periods stop permanently and cause the psychological symptom, anxiety. This study applied explanatory research design with Cross-sectional approach. This study also involved 197 female menopause in 11 villages in Diwek – Jombang Regency. The participants were selected using Cluster Random Sampling. The independent variables were individual factor, social network, stress, social support, and stress evaluation while dependent variable was anxiety. The data were collected by using structured questionnaire and then analyzed by using Partial Least Square test. The results of the study showed that (1) individual factor did not significantly influence social network (path coefficient of 0.054, t=0.75); (2) social network did not significantly influence stress (path coefficient of -0.161, t=2.28); (3) stress did not significantly influence social support (path coefficient of -0.026, t=0.37); (4) individual factor significantly influenced stress evaluation (path coefficient of -0.056, t=3.74); (5) social network significantly influenced stress evaluation (path coefficient of -0.147, t=2.13); (6) stress did not significantly influence stress evaluation (path coefficient of 0.022, t=0.32); (7) social support significantly influenced stress evaluation (path coefficient of -0.117, t=2.02); (8) social support significantly influenced anxiety (path coefficient of -0.326, t=5.25); and (9) stress evaluation significantly influenced anxiety (path coefficient of 0.196, t=9.07). Social support is highly recommended to decrease anxiety among female menopauses by promoting stress evaluation and social support from close relations.